Opium poppy capsule growth and alkaloid production is constrained by shade during early floral development. (24th February 2020) - Hope, Elliana; Carins‐Murphy, Madeline R.; Hudson, Corey; Baxter, Les; Gracie, Alistair
Abstract: Morphinan alkaloids accumulate in the capsules of Papaver somniferum L. (opium poppy) most likely as defence against herbivory. Thus, capsule size is an important component of alkaloid yield. Shade during early cell division‐dominated growth of reproductive structures generally reduces final fruit size more than shade during later cell expansion‐dominated growth. The current study aimed to determine whether this response is found in opium poppy and the subsequent impact on alkaloid yield, composition and seed production. First the timing of key reproductive developmental events was resolved relative to macromorphological traits. Plants were then shaded during either (a) floral initiation, (b) early floral development or (c) capsule expansion before being harvested at maturation. Shade during floral initiation dramatically reduced final capsule size, alkaloid yield and seed number, and increased the concentration of precursor compounds relative to morphine, despite plants later returning to full sun. Shade during later capsule growth enhanced capsule size and alkaloid yield but had little effect on alkaloid composition or seed number. Thus, early developmental processes, including morphine biosynthesis, appear to have a relatively greater demand for carbohydrates compared with later processes. Crop management practices and environmental factors that limit carbohydrate availability during early development are thus predicted to have significant negative impacts on alkaloid production and reproductive success. Abstract : Shade applied during floral initiation dramatically reduced final capsule size, alkaloid yield and seed number, and increased the concentration of precursor compounds relative to morphine, despite plants later returning to full sun.